Paul's "?????? ??????? " as a fundamental factor for peaceful co-existence in multi-religious societies - Augustine Thang Zawm Hung (Jurnal Teologi (Journal of Theology), 2015)
Although religions teach peace, hope and love, massive acts of violence have been taking place in their names. Any religion can become a home of violence and fanaticism, and Christianity is no exception. The sacred texts of a religion influence and determine the views of an adherent on the world and other human beings. It is the sacred scripture that governs the life and world views of a Christian. This article treats the debates of the scholars on the Pauline usage of "?????????????" and proposes a relevant interpretation which will help the Church's peaceful co-existence in multi-religious societies.